cCPE Fusion Proteins as Molecular Probes to Detect Claudins and Tight Junction Dysregulation in Gastrointestinal Cell Lines, Tissue Explants and Patient-Derived Organoids - Ayk Waldow; Laura-Sophie Beier; Janine Arndt; Simon Schallenberg; Claudia Vollbrecht; Philip Bischoff; Martí Farrera-Sal; Florian N. Loch; Christian Bojarski; Michael Schumann; Lars Winkler; Carsten Kamphues; et al. (MDPI AG, 2023)
Claudins regulate paracellular permeability, contribute to epithelial polarization and are dysregulated during inflammation and carcinogenesis. Variants of the claudin-binding domain of Clostridium perfringens enterotoxin (cCPE) are highly sensitive protein ligands for generic detection of a broad spectrum of claudins. Here, we investigated the preferential binding of YFP- or GST-cCPE fusion proteins to non-junctional claudin molecules. Plate reader assays, flow cytometry and microscopy were used to assess the binding of YFP- or GST-cCPE to non-junctional claudins in multiple in vitro and ex vivo models of human and rat gastrointestinal epithelia and to monitor formation of a tight junction barrier. Furthermore, YFP-cCPE was used to probe expression, polar localization and dysregulation of claudins in patient-derived organoids generated from gastric dysplasia and gastric cancer. Live-cell imaging and immunocytochemistry revealed cell polarity and presence of tight junctions in glandular organoids (originating from intestinal-type gastric cancer and gastric dysplasia) and, in contrast, a disrupted diffusion barrier for granular organoids (originating from discohesive tumor areas). In sum, we report the use of cCPE fusion proteins as molecular probes to specifically and efficiently detect claudin expression, localization and tight junction dysregulation in cell lines, tissue explants and patient-derived organoids of the gastrointestinal tract.